INR Telemonitoring: Efficacy and Safety of a Telemonitoring Program in 453 Patients - Ferreira, Filipa (2012)
Introduction: The INR analyses of patients taking oral anticoagulants brings great burden to healthcare professionals, overspending founds from the National Health Service (NHS) and loss of quality of life of patients who are forced to frequent hospital visits. It should not be surprising that the technology is at the forefront of health care nowadays and some projects have been developed in the area of anticoagulation for INR self-monitoring by telephone, mobile phone or internet. The aim of this study was to assess the efficacy and safety of an INR telemonitoring system that was implemented in our hospital in 2006. Methods: A prospective, observational study of 453 patients who were included in this telemonitoring system from 2006 until late November 2010. The communication between patients and health professionals was done via mobile phone messages in a standardized and codified system that included information about maintenance or modification of therapy and the date of the next evaluation. When necessary the patient could send a request for help through a code for that purpose. In the studied population the following parameters were evaluated: withdrawal of the telemonitoring project, need for change of anticoagulant dose, requests for clarification by the patient, hospitalization for bleeding complications and INR > 10. Results: In our study population 53% were female, mean age = 57 +/- 16 years. The percentage of INR values within the therapeutic range was 83%. There were no dropouts of the telemonitoring project. The percentage of patients with major and minor bleeding complications during follow-up was 0.4% and 0.2% respectively. Conclusions: The telemonitoring system proves safe and effective remote monitoring of INR analysis, allowing efficient monitoring of INR with low prevalence of major or minor bleeding.